Effect of Raising Laying Hens in Intensive, Continuous and Rotational Free-Range Systems on Egg Production and Yolk Cholesterol Content - Khatifah Khatifah; Agni Ayudha Mahanani; Muhammad Salihin (Jurnal Agripet)
This study aimed to evaluate the effects of raising laying hens in intensive cage and various free-range systems on hen-day production (HDP), egg weight, egg mass, yolk cholesterol, and yolk protein content. A total of 80 Isa Brown laying hens, aged 15 weeks and with an average starting weight of 1.20 kg, were assigned to four different rearing treatments: P1 (intensive cage system), P2 (continuous free-range system), P3 (rotational free-range system with two relocations), and P4 (rotational free-range system with four relocations), each with four replicates. Data were analyzed using analysis of variance (ANOVA), and significant differences (P0.05) among treatments were further evaluated using Duncan's multiple range test. The results showed that the rearing system significantly influenced daily body weight gain (DBWG), daily feed intake (DFI), HDP, egg weight, egg mass, feed conversion ratio (FCR), and yolk cholesterol content (P0.05), but had no significant effect on yolk protein content (P0.05). In conclusion, continuous free-range systems led to higher HDP and egg mass, while the intensive cage system resulted in greater egg and body weight, along with higher feed intake. The continuous free-range system was associated with a lower FCR, and the rotational free-range system with four relocations yielded the lowest yolk cholesterol levels.